Rebelião em Penitenciárias de Mato Grosso do Sul: o enquadramento de uma crise pelo jornal Correio do Estado - Claudenir dos Santos (2021)
The research aims to analyze the frameworks used in the journalistic coverage of the prisoners' rebellion in Mato Grosso do Sul, which occurred in May, 2006. The rebellion was marked by the appropriation of several state prison establishments, riots, threats to state security bodies, deaths, kidnappings and social panic. In Mato Grosso do Sul, they emerged as a result of violent events that occurred in São Paulo and Paraná, whose authorship was attributed to the criminal organization Primeiro Comando da Capital (PCC). In order to carry out the research, the content produced by the newspaper Correio do Estado, in Campo Grande / MS, was taken in the period between 05/14/2006, the date on which the rebellions started, on 06/14/2006. A combination of exploratory research methods and analysis of the data obtained from the perspective of news framing (media frames) proposed by Robert Entman (1993) was used. The results show that in the narrative used, there was a predominance of an attempt to delegitimize the public administration and a political criticism of the current state control and the social aspects of violence and prison were suppressed.